Asymmetric flavone-based liquid crystals: synthesis and properties. Issue 9 (15th July 2017) - Timmons, Daren J.; Jordan, Abraham J.; Kirchon, Angelo A.; Murthy, N. Sanjeeva; Siemers, Troy J.; Harrison, Daniel P.; Slebodnick, Carla
ABSTRACT: A series of flavones ( n -F ) substituted at the 4′, and 6 positions was prepared, characterised by NMR ( 1 H, 13 C), HRMS, and studied for liquid crystal properties. The 4′-alkoxy, 6-methoxyflavones (4-F–16-F ) exhibit varying ranges of nematic and smectic A phases as evidenced by polarised optical microscopy and differential scanning calorimetry (DSC). As the tail length is increased, the smectic phase becomes more prevalent. Smectic phases for (8-F–16-F ) were further analysed by powder X-ray diffraction (XRD), and the rate of structural transformations was explored by combined DSC/XRD studies. Flavonol6-F–OH was also prepared but no mesogenic behaviour was observed. The molecular structures of6-F and6-F–OH were determined by single-crystal XRD and help to explain the differences in material properties. Additionally, fluorescence and electrochemical studies were conducted on solutions of n -F . Graphical Abstract: